Spironolactone Induces Vasodilation by Endothelium-Dependent Mechanisms Involving NO and by Endothelium-Independent Mechanisms Blocking Ca2+ Channels - Margarida Lorigo; João Amaro; Elisa Cairrao (MDPI AG, 2024)
Background: Spironolactone (SPI) is a diuretic widely used to treat cardiovascular diseases (CVD) and is non-specific for mineralocorticoid receptors (MR) and with an affinity for progesterone (PR) and androgen (AR) receptors. Since 2009, it has been suggested that pharmaceuticals are emerging contaminants (called EDC), and recently, it was reported that most EDC are AR and MR antagonists and estrogen receptors (ER) agonists. Concerning SPI, endocrine-disrupting effects were observed in female western mosquitofish, but there are still no data regarding the SPI effects as a possible human EDC. Methods: In this work, aortic rings were used to analyze the contractility effects of SPI and the mode of action concerning the involvement of Ca2+ channels and endothelial pathways. Moreover, cytotoxic effects were analyzed by MTT assays. Results: SPI induces vasodilation in the rat aorta by endothelium-dependent mechanisms involving NO and by endothelium-independent mechanisms blocking Ca2+ channels. Moreover, a non-monotonic effect characteristic of EDC was observed for SPI-induced decrease in cell viability. Conclusions: Our findings suggest that SPI may act as an EDC at a human level. However, ex vivo studies with human arteries should be carried out to better understand this drug's implications for human health and future generations.